2018
DOI: 10.1093/alcalc/agx113
|View full text |Cite|
|
Sign up to set email alerts
|

Alcohol Use in Adolescence and Later Working Memory: Findings From a Large Population-Based Birth Cohort

Abstract: AimsThe study aimed to examine the association between adolescent alcohol use and working memory (WM) using a large population sample.MethodsData from the Avon Longitudinal Study of Parents and Children were used to investigate the association between alcohol use at age 15 years and WM 3 years later, assessed using the N-back task (N ~ 3300). A three-category ordinal variable captured mutually exclusive alcohol groupings ranging in order of severity (i.e. low alcohol users, frequent drinkers and frequent/binge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 65 publications
2
17
3
Order By: Relevance
“…Unlike the studies that have demonstrated a prospective association between binge drinking and cognitive functioning in adolescence e.g. (17)(18)(19)(20), we found little evidence in support of this association. The contrast in findings could be due to a number of possibilities.…”
Section: Comparison With Previous Studiescontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike the studies that have demonstrated a prospective association between binge drinking and cognitive functioning in adolescence e.g. (17)(18)(19)(20), we found little evidence in support of this association. The contrast in findings could be due to a number of possibilities.…”
Section: Comparison With Previous Studiescontrasting
confidence: 99%
“…Third, as alcohol use behaviours typically change over time (46), repeated measures of binge drinking were used in this study to capture heterogenous patterns across this sensitive period in comparison to our previous study which assessed alcohol use on one occasion (17). Finally, most of the previous studies (18)(19)(20) assessed cognitive functioning using a range of measures .…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing data from 3,141 adolescents, frequent binge drinkers exhibited poorer working memory compared to the low alcohol group. However, this association was attenuated when adjusting for sociodemographic variables, tobacco, and cannabis use (52). In a sample of 89 young people who did not have a history of psychiatric disorders and did not regularly consume other drugs, consistent binge drinking over two years in late adolescence was associated with poorer immediate and delayed recall, retention, and working memory, compared to non-binge drinkers (53).…”
Section: Neuropsychological Consequences Of Alcohol Usementioning
confidence: 90%
“…The N-back task (2-back condition) was used to assess working memory. The N-back task (38) is widely used to measure working memory (39)(40)(41). A measure of discriminability (d′) was chosen as the primary outcome measure given it is an overall performance estimate.…”
Section: Working Memorymentioning
confidence: 99%